Influence of nitrogen sources and varieties on nitrogen and micronutrient uptake in aerobic rice (Oryza sativa) - Baghel, Jitesh Kumar; Singh, Y.V.; Abraham, G.; Kumar, Dinesh; Gupta, Navindu (Annals of Agricultural Research, 2016)
A field experiment was conducted during the Kharif season of 2010 at New Delhi to study theÂ influence of aerobic rice varieties and nitrogen sources on plant nutrient uptake and productivity.Â The experiment was laid out with 16 treatment combinations including four rice varieties viz.,Â ’Jaldi Dhan 13; Pusa Sugandh 5; Anjali and Pusa 834 and four nitrogen application options viz.,Â control (N0P60K40); 120 kg N haâ€“1 through urea; 60 kg N haâ€“1 through urea + 60 kg N haâ€“1 throughÂ vermicompost and 90 kg N haâ€“1 through urea + 30 kg N haâ€“1 through vermicompost. The crop wasÂ direct seeded with a row spacing of 25 cm. Nitrogen was applied through urea and vermicompost.Â The field was kept under non-saturated aerobic condition throughout the crop growing season.Â The results showed that rice variety ’Pusa Sugandh 5’ gave significantly higher grain and strawÂ yield over other varieties. The grain and straw yield were significantly enhanced due to integratedÂ application of N through urea and vermicompost (75:25) as compared to other doses of N. RiceÂ varieties showed significant difference in uptake of N, Fe, Zn, Mn and Cu in grain and straw. ThereÂ was significant increase in uptake of N, Fe, Zn, Mn and Cu in grain and straw due to the integratedÂ application of N through 3 different combinations of urea and vermicompost over the control. TheÂ combination of 90 kg N (urea) + 30 kg N (VC) haâ€“1 had highest uptake of N, Fe, Zn, Mn and CuÂ followed by 60 kg N (urea) + 60 kg N (VC) and 120 kg N (urea).